Study on the Response Law of Pipeline Damage Size based on Ultrasonic Guided Waves - Wei, Gaoneng; Shi, Mingjiang (Scientific Journal of Technology, 2026)
To address the difficulty of quantitatively evaluating early-stage damage in in-service metallic pipelines, this study establishes a three-dimensional transient finite element model of a pipeline based on the low-dispersion L(0,2) ultrasonic guided-wave mode excited at 70 kHz. The effects of circumferential damage size, depth, and axial length on echo characteristics are investigated in detail. The results show that, with the damage position kept constant, both the damage echo amplitude and the reflection coefficient increase significantly with the growth of circumferential coverage, while the increasing trend gradually slows in the large-coverage range. When the damage depth increases from 25% to 100%, the reflected echo energy continues to rise, indicating that the L(0,2) mode is highly sensitive to wall-thinning damage. By contrast, when the axial length varies from 1 mm to 5 mm, the reflection coefficient changes only slightly, suggesting that this mode is not sensitive to the axial length of damage. These findings demonstrate that circumferential size and damage depth are the dominant factors affecting guided-wave echo intensity, and they can provide a basis for quantitative damage evaluation and feature selection in pipelines.